Metronomic chemotherapy for advanced diffuse hepatocellular carcinoma in a dog - Silva, Paloma Helena Sanches da; Souza, Mayara Coutinho Carlos de; Cavalcanti, Ellen Bethânia de Oliveira; Fonseca, Victoria Bringhenti; Silveira, Tatiany Luiza; Flecher, Mayra Cunha; Cassali, Geovanni Dantas; Horta, Rodrigo dos Santos (Brazilian Journal of Veterinary Pathology, 2021)
Primary liver tumors represent 0.6% to 1.3% of neoplasms in dogs. Hepatocellular carcinoma (HCC) is the most common liver tumor. It is divided into three morphological groups: massive, nodular and diffuse. The presumptive diagnosis is made through imaging tests, such as ultrasound, although confirmation is made by histopathology. Surgery remains the treatment of choice for massive tumors, but there is no standard treatment for nodular and diffuse forms. This study aimed to report a case of prolonged survival in a dog with diffuse HCC, treated with metronomic chemotherapy and palliative care including non-steroidal anti-inflammatory and low-dose naltrexone.